CHANGE THAT DRIVES INNOVATIVE MANAGEMENT: A CASE STUDY - Noviaty Kresna Darmasetiawan (Journal of Management and Business, 2008)
Innovation requires change. In the business environment, resistance to change is deleterious to organizations. The ability to continuously adapt to change enables firms to achieve sustainable value creation and competitive advantage. Major organizational changes for innovation can anticipate resistance, especially if proposed changes alter values and visions related to the existing order. Change may be viewed in terms of the alteration in activities and tasks of the organization. These may range from subtle modifications in procedures and operations (such as continuous improvement or small incremental steps); to transformational radical changes (such as rapid expansion into international markets, mergers or major restructuring in an organization). On the other hand, for firm to be innovative there must be awareness throughout the organization of the need for innovation. Along with the streamlining of operations and processes to improve product and service delivery, the mindset of employees needs to change. Since innovation is an important factor for future growth of any business venture, change management is required for achieving the required business strategies and practices. This case study was conducted to review change that drives innovative management. It was an exploratory study and had been done by using semi-structured interviews with ten managers. The research questions explored were: What were the drivers of change? How did the drivers support organizational objectives and goals? And what was the resistance to change? This firm had Continuous Innovation or Improvement for its corporate culture, and this research showed that it was the most important driver for its change. It was also found that the most important ingredient for successful change management was employee involvement. Therefore, management should pay more attention to human dimensions when implementing change. They have to invest more time in communicating, training and following up on the change system or process. It is important for management to seek and take into consideration the input from employees into procedures for implementing change.